Thucydides on strategy : athenian and spartan grand strategies in the peloponesian war and their relevance today - Koliopoulos, Constantinos; Platias, Athanassioss G. ([S.l.] : Columbia University Press, 2010)
Masterfully crafted and surprisingly modern, Thucydides's History of the Peloponnesian War has long been celebrated as an insightful, eloquent, and exhaustively detailed work of classical Greek history. Scholars have also admired the text's deep political and military dimensions. Written in the fifth century B.C.E., the History of the Peloponnesian War has been placed alongside Sun Tzu's The Art of War and Carl von Clausewitz's On War as one of the great treatises on strategy. The perfect companion to Thucydides's impressive text, this volume details the strategic concepts at work within the History of the Peloponnesian War and demonstrates how, through case studies of recent conflicts in Kosovo, Afghanistan, and Iraq, Thucydidean thought remains vital to the analysis of strategic operations. Some scholars have credited Thucydides with founding the discipline of international relations. Written by scholars with extensive experience in this and related fields, Thucydides on Strategy situates the historian solidly within the annals of classical history and within the world of modern war.
Keywords: Greece; Historiography; History of the Peloponnesian War (Thucydides); Peloponnesian War (Greece : 431-404 B.C.); Political and social views; Thucydides